(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The aim of this study was to investigate the relationship between self-esteem, emotional intelligence and burnout in a sample of employees from education faculty at Tishreen University. The sample consisted of (70) employees. A refereed version of Rosenberg Self-Esteem Scale (Rosenberg,1965),and a version of Maslach and others Scale to asses burnout (MBI; Maslach, Jackson,& Leiter,1996) but emotional intelligence was measured by a version of Wong and Law Scale (WLEIS; Wong & Law, 2002).Results indicated: • There was a statistical significant negative relationship between the degrees of employees in burnout and their degrees in self-esteem and in the emotional intelligence, whereas it was positive between their degrees in self-esteem and their degrees in emotional intelligence. • There were no statistically significant differences between the mean scores of male and female in burnout, in self-esteem and in emotional intelligence. • Emotional intelligence and self-esteem could contribute significantly to the prediction of burnout.